Partial Discharge Characterization based on Leakage Current Pulses Waveform for Contaminated Glass Insulator String - N. A. Othman; M. A. M. Piah; Z. Adzis; Nasir A. Al-geelani (Institute of Advanced Engineering and Science, 2016)
This paper deals with the analysis of partial discharge (PD) occurrences based on leakage current (LC) pulses distribution under different level of contamination. In this work, laboratory based contamination performance tests are conducted on four units of glass insulator string stacked in I-position. Results show that PD can be characterized (according to their occurrence with respect to the AC supply) as follows: corona discharge occurring dominantly in lightly contaminated insulators, surface discharge occurring dominantly in medium contaminated insulators and finally internal discharge occurring dominantly in heavily contaminated insulators. The ability to distinguish the type of PDs from the LC waveform could be used to monitor and predict the condition of the insulator. The outcome can be incorporated in a conditioning monitoring system.